Abolishing capital punishment in Uzbekistan: between external pressure and pragmatism - Ismatov, Aziz (Zeitschrift für die gesamte Strafrechtswissenschaft, 2018)
Uzbekistan de jure abolished the death penalty in 2008. Until then, only a few people had predicted that, despite widespread support for the death penalty, President Karimov would support the path to abolition. On the eve of the tenth anniversary of abolition, a general debate on the exact reasons behind the continued existence on the one hand and abolition of capital punishment on the other still remains open. This article will investigate the theories that contributed to the abolition of capital punishment in Uzbekistan. A detailed and coherent discussion of the evolution of the laws governing the death penalty, the public opinion influence, and political preconditions will shed more light on the process of abolition.